Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ). Issue 2 (20th January 2023) - Warneke, Carsten; Schwarz, Joshua P.; Dibb, Jack; Kalashnikova, Olga; Frost, Gregory; Al‐Saad, Jassim; Brown, Steven S.; Brewer, Wm. Alan; Soja, Amber; Seidel, Felix C.; Washenfelder, Rebecca A.; Wiggins, Elizabeth B.; et al.
Abstract: The NOAA/NASA Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ) experiment was a multi‐agency, inter‐disciplinary research effort to: (a) obtain detailed measurements of trace gas and aerosol emissions from wildfires and prescribed fires using aircraft, satellites and ground‐based instruments, (b) make extensive suborbital remote sensing measurements of fire dynamics, (c) assess local, regional, and global modeling of fires, and (d) strengthen connections to observables on the ground such as fuels and fuel consumption and satellite products such as burned area and fire radiative power. From Boise, ID western wildfires were studied with the NASA DC‐8 and two NOAA Twin Otter aircraft. The high‐altitude NASA ER‐2 was deployed from Palmdale, CA to observe some of these fires in conjunction with satellite overpasses and the other aircraft. Further research was conducted on three mobile laboratories and ground sites, and 17 different modeling forecast and analyses products for fire, fuels and air quality and climate implications. From Salina, KS the DC‐8 investigated 87 smaller fires in the Southeast with remote and in‐situ data collection. Sampling by all platforms was designed to measure emissions of trace gases and aerosols with multiple transects to capture the chemical transformation of these emissions and perform remote sensing observations of fire and smoke plumes under day and night conditions. The emissions were linked to fuels consumed and fire radiative power using orbital and suborbital remote sensing observations collected during overflights of the fires and smoke plumes and ground sampling of fuels. Plain Language Summary: The NOAA/NASA Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ) experiment was aimed at understanding how fuel and fire conditions at the point of emission influence the chemistry of smoke, what conditions and processes control the rise of smoke plumes, what happens to smoke as it is distributed in the atmosphere, and how chemical transformation of smoke impacts air quality, weather, and climate downwind. Lessons learned from FIREX‐AQ will also be used to assess and improve the effectiveness of satellites for estimating the emissions from wildfires and prescribed burns and to reduce uncertainties associated with modeling and forecasting of smoke. Here we present an overview of the FIREX‐AQ effort, its motivation and design, with detailed descriptions of the measurements and analyses carried out, their connections to FIREX‐AQ science goals, and the early findings of this exceptionally broad effort to understand fire and its many impacts on the atmosphere. Key Points: This work is an overview of the NOAA/NASA Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ) field experiment FIREX‐AQ investigated biomass burning emissions and chemistry and smoke transport FIREX‐AQ was a multi‐platform mission that also utilized fire modeling and satellite detections and validation